(untitled) (Research, Society and Development, 2020)
Objective: to verify the association between bacteriological profile and variables related to neoplastic wounds of patients under palliative care. Method: Cross-sectional study, with a sample composed of 36 patients admitted to the wards of the National Cancer Institute José Alencar Gomes da Silva - Unit IV. Data collection took place between the months of October and December 2018, using a specific form. In the data analysis, descriptive measures and Fischer/chi-square test were used at the 5% significance level (α = 0.05). Results: The sample was composed by 36 individuals, 19 (52.78%) of whom were female, with a predominant percentage of metastasis formation (63.89%). There is a strong association between the variables palliative radiotherapy and the presence of Pseudomonas sp. (p = 0.02), type of primary tumor and the presence of Citrobacter sp. and Acinetobacter sp. (p <0.001) and location of the neoplastic wound in the presence of Citrobacter sp. (p = 0.03) and Acinetobacter sp. (p = 0.01). Palliative chemotherapy does not favor an increase in biofilm in the neoplastic wound, and it is not associated with any bacterial genus. The main bacteria identified were Pseudomonas sp., Morganella sp., Klebsiella sp. and Proteus sp.. Conclusion: the treatment with radiotherapy, the type of primary tumor and the location of the tumor wound have a significant association with the bacteriological profile of the lesions and, therefore, the collection of swab and antibiogram analysis of the neoplastic wounds is recommended to improve nursing care .